A Case Report on Secondary Infection in a -2-Year -Male Old Child Treated with Topical Scabicidal Agent - Clement, Kabakama`C.; Chandrasekar, Keerthana (Indian Journal of Pharmacy Practice)
Scabies is one of the common dermatological conditions accounting for a substantial proportion of skin disease in developing countries caused by the microscopic mite Sarcoptes scabiei var. hominis. Comes from the latin word “Scabere” which means to scratch commonly known as the seven-year itch. The Human Scabies mite infestation will present to the patients with the following symptoms such as the erythematosus vesicles, papules on torso extremities and some with the adjacent linear excoriations. Scabies treatment include administration of scabicidal agent, However treatment failures are uncommon but may occur due to improper application, resistance of the topical therapy and reinfestation .A- 2 -Year old Male Child was admitted to pediatric ward at the Government District Headquarters Hospital with complaint of diffuse maculopapular rash according to the signs and symptoms Child was diagnosed with scabies/wheezing associated lower Respiratory Tract infections. The mainstay of scabies treatment is the application of topical Scabicidal agent. Permethrin 5% lotion is the treatment of choice which acts as a neurotoxin that causes paralysis and death in ectoparasites and causes disruption of sodium ion influx through cell membrane channels by which membrane repolarization is regulated and delayed repolarization which results in paralysis of nerves in exoskeletal respiratory muscles of parasite leading to death. The lotion should be applied over the entire body including the face and scalp in infants. It should be left on for 8 h up to 12 h and then rinsed. Reapplication one week later is advised. This Case report focuses on the use of permethrin and crotamiton lotions for the treatment of secondary infections due to scabies infestation in Paediatric Population.
Keywords: Maculopapular Rash; Scabies; Permethrin 5% lotion; Pediatrics.